AGENCY COSTS DAN KEBIJAKAN DIVIDEN PADA EMERGING MARKET - Darman Darman (University of Merdeka Malang, 2008)
The purpose of this research was to analyze agency costs and dividend policy onemerging market. The research population was 147 manufacture industry companies listedat the Indonesian Stock Exchange. Sample were retrieved bases on purposive sampling method,there were 25 companies, which were fulfilling the condition needed, starting from 2000until 2005, pooling data with analysis unit n = 6 x 25 = 150. Research used ordinary leastsquare. Research results showed that agency costs did not significantly influence dividendpolicy. Research conclusion was that agency costs were not important factors of dividendpolicy. Next analysis result showed that insider ownership, institutional ownership, dispertionof ownership, and free cash flow did not significantly influence dividen policy. Thecollateralizable asset significantly influenced dividend policy. This finding showed that therewas no agencial conflicts between manager (agent) and stockholders (principals) in emergingmarket (manufacture industry companies listed at the Indonesian Stock Exchange). However,there were agencial conflicts between stockholders and creditor (bondholders).